3D Numerical Modelling of Mould Filling of a Coat Hanger Distributer and Rectangular Cavity - Rao, Rekha R.; Mondy, Lisa A.; Noble, David R.; Hopkins, Matthew M.; Brooks, Carlton F.; Baer, Thomas A. (IntechOpen, 2012)
None